2021
DOI: 10.1136/jitc-2021-002591
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of regulatory T cell infiltration in tumors: implications for innovative immune precision therapies

Abstract: With the broad application of cancer immunotherapies such as immune checkpoint inhibitors in multiple cancer types, the immunological landscape in the tumor microenvironment (TME) has become enormously important for determining the optimal cancer treatment. Tumors can be immunologically divided into two categories: inflamed and non-inflamed based on the extent of immune cell infiltration and their activation status. In general, immunotherapies are preferable for the inflamed tumors than for non-inflamed tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(99 citation statements)
references
References 140 publications
1
75
0
Order By: Relevance
“…Our results demonstrate that dietary BRB-E significantly inhibits CD4 + FoxP3 + Treg accumulation within the primary tumors of the oral cavity, as evidenced by a reduction in Treg numbers as well as by decreased mRNA transcripts in the tongue for Foxp3 and Ctla4 , markers indicative of Treg recruitment and activity ( 18 ). Mechanisms that mediate this reduced recruitment of Tregs to HNSCC tumor microenvironments following BRB-E administration are still under active investigation, although chemokine-dependent infiltration via Ccl1, Ccl18, and Ccl22, and Vegfa-dependent recruitment are potential mechanisms ( 41 ). Indeed, BRB has been shown to inhibit angiogenesis in oral and esophageal cancers ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that dietary BRB-E significantly inhibits CD4 + FoxP3 + Treg accumulation within the primary tumors of the oral cavity, as evidenced by a reduction in Treg numbers as well as by decreased mRNA transcripts in the tongue for Foxp3 and Ctla4 , markers indicative of Treg recruitment and activity ( 18 ). Mechanisms that mediate this reduced recruitment of Tregs to HNSCC tumor microenvironments following BRB-E administration are still under active investigation, although chemokine-dependent infiltration via Ccl1, Ccl18, and Ccl22, and Vegfa-dependent recruitment are potential mechanisms ( 41 ). Indeed, BRB has been shown to inhibit angiogenesis in oral and esophageal cancers ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, increasing studies observed that tumor-associated macrophages were associated with tumor-promoting inflammation and may favor tumor initiation and progression ( Mantovani et al, 2017 ; Ngambenjawong et al, 2017 ). Meanwhile, high-level intratumoral Tregs designed a generalized immunosuppressive tumor microenvironment and protected tumor cells from the host’s immune surveillance ( Nishikawa and Koyama, 2021 ). Previous study proposed that the presence of B cells in tumors was associated with a better prognosis for patients receiving immunotherapy, and they speculate that B cells may support CD8+T cells to effectively fight tumor cells ( Cabrita et al, 2020 ; Petitprez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the infiltration of cytotoxic T cells and memory T cells was associated with good prognosis in gastric patients ( Chang et al, 2014 ). Although the current tumor immunotherapy targets mainly focus on CD8 + T cells, the role of conventional CD4 + T cells in tumor immunity has gradually attracted attention ( Nishikawa and Koyama, 2021 ). CD4 + effector T cells can enhance immunity by regulating dendritic cells or stimulating other proinflammatory cells of the myeloid lineage ( Behrens et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%